2016
DOI: 10.1016/j.jcm.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Pyrophosphate Dihydrate Crystal Deposition Disease Simulating Osteoarthrosis of the Knee: A Case Report

Abstract: Objective: The purpose of this case report is to describe a case where calcium pyrophosphate dehydrate crystal deposition disease (CPPD) simulated osteoarthritis of the knee. Clinical Features: A 78-year-old woman had a 2-week history of severe right knee pain accompanied by mild swelling. The onset was sudden and did not involve a history of trauma or previous injury to the right knee. Inspection and palpation revealed pain along the medial joint line and marked difficulty ambulating. Results of Lachman's tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
1
0
2
Order By: Relevance
“…Процесс активации NLRP3-инфламмасомы является ключевым в развитии кристалл-ассоциированной воспалительной реакции. Он представляет собой патофизиологическую основу возникновения острого микрокристаллического артрита [21,22] и позволяет обосновать применение противовоспалительных препаратов, включая ингибиторы ИЛ-1 [23]. Известно, что БДПК с наибольшей частотой встречается у лиц пожилого (как правило, старше 65 лет) и старческого возраста [24][25][26].…”
Section: Discussionunclassified
“…Процесс активации NLRP3-инфламмасомы является ключевым в развитии кристалл-ассоциированной воспалительной реакции. Он представляет собой патофизиологическую основу возникновения острого микрокристаллического артрита [21,22] и позволяет обосновать применение противовоспалительных препаратов, включая ингибиторы ИЛ-1 [23]. Известно, что БДПК с наибольшей частотой встречается у лиц пожилого (как правило, старше 65 лет) и старческого возраста [24][25][26].…”
Section: Discussionunclassified
“…A patient may demonstrate several different clinical patterns during the course of CPPD disease; pseudogout, pseudo-rheumatoid arthritis, pseudo-osteoarthritis (with acute exacerbations), pseudo-osteoarthrosis (without acute exacerbations), pseudo-neuropathic osteoarthropathy, and miscellaneous pattern ( 2 ). The most common pattern is pseudo-osteoarthritis, which is caracterised by chronic progressive arthritis with superimposed acute inflammatory episodes in large joints such as the knee and hip ( 2 ). Although osteoarthritis and CPPD are distinct disorders, it has been suggested that destruction of the articular cartilage caused by the crystals may predispose a patient to developing secondary osteoarthritis ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Durchschnittliche Häufigkeiten der klinischen Manifestationen bei HH[28,[34][35][36][37][38][39][40][41].…”
unclassified